2006
DOI: 10.1203/01.pdr.0000227442.78881.47
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Creatine Kinase Activity by Cystine in the Kidney of Young Rats

Abstract: Nephropathic cystinosis is a lethal genetic disease caused by a lysosomal transport disorder leading to intralysosomal cystine accumulation in all tissues. Cystinosis is the most common inherited cause of Fanconi syndrome, but the mechanisms by which cystine causes tissue damage are not fully understood. Thiolcontaining enzymes are critical for renal energy metabolism and may be altered by disulfides like cystine. Therefore, in the present study our main objective was to investigate the in vivo and in vitro ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Without treatment, most children with cystinosis develop renal failure, visuospatial difficulties, and increasing discrepancy in a progressive cognitive impairment due to cystine accumulation in the brain [4,5]. Accumulated data indicated that at the molecule level, the high concentration of intracellular cystine affected the activity and functions of many thiol-containing enzymes, such as pyruvate kinase and creatine kinase [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without treatment, most children with cystinosis develop renal failure, visuospatial difficulties, and increasing discrepancy in a progressive cognitive impairment due to cystine accumulation in the brain [4,5]. Accumulated data indicated that at the molecule level, the high concentration of intracellular cystine affected the activity and functions of many thiol-containing enzymes, such as pyruvate kinase and creatine kinase [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that BBCK is one of the targets of oxidative stresses induced by dis- eases or toxins. Particularly, BBCK inactivation by cystine and cystine dimethyl ester (CDME) has been observed by in vivo studies [6][7][8][9]21,22], while the other CK isoforms seem not to be affected during the pathogenesis of cystinosis [23]. The in vivo studies suggest that cystine or CDME may affect enzyme activity by the induction of free radicals and lipoperoxidation production, the increase of carbonylation of proteins and the decrease of thiol/disulfide ratio [24].…”
Section: Introductionmentioning
confidence: 99%
“…It catalyzes the reversible transfer of the phosphoryl group from phosphocreatine to ADP, regenerating ATP. For this enzyme there is the mitochondrial isoform (mitCK), which uses ATP to form phosphocreatine and ADP, and the cytosolic isoform (cytCK) that forms creatine through phosphocreatine, generating ATP (Ferreira, 2014;Rech et al 2006Rech et al , 2018. Mg 2+ -ATPase is localized in the plasma membrane of renal and hepatic cells and is essential because it carries the Mg 2+ that is the cofactor of several enzymes involved in energy metabolism (Nozadze et al 2015).…”
Section: Introductionmentioning
confidence: 99%